Penggunaan Media Wattpad dalam Pembelajaran Daring Menulis Cerita Pendek di SMAN 1 Abiansemal - Layinah, Sahlatul; Wendra, I Wayan; Yasa, I Nyoman (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This research describes the use of wattpad media in online learning to write short stories. This research uses a qualitative descriptive design. The aim of this research is to find out the step for using wattpad media in online learning, learning outcomes of class XI IPA students and obstacles experinced by teachers in learning using wattpad media at SMAN 1 Abiansemal. Data collection was carried put using the observation method, assignment method, and interview method. The instruments used are observation guidelines, assessment formats, and interview guidlines. The result of this research is that there are steps to use wattpad media in online learning to wite short stories. Apart form that, this research shows that student learning outcomes using wattpad media as an online learning medium for writing short stories are 1.723. if these amounts are averaged, a value of 75 will appear in the good category. Several obstacles were found that teachers experienced when online learning using wattpad media took place. It is hoped that the results of this research will provide benefits to students in learning to write short stories, so that students can find new media for writing short stories.